Hydrogeochemical studies of groundwater in semi-arid areas of northern Ethiopia using geospatial methods and multivariate statistical analysis techniques - Haftay Hailu; Solomon Haftu (Applied Water Science, 2023)
Abstract The present study focused on evaluating the groundwater hydrogeochemical of shallow aquifers in the semi-arid areas of northern Ethiopia, using geospatial modelling and multivariate statistical techniques. Physico-chemical parameters, including pH, major ions, electrical conductivity (EC), total dissolved solids (TDS), total hardness (TH), pollution index (PI) and other parameters, from 22 samples have been used to assess water quality, sources of various ions, water types and factors controlling groundwater chemistry. Results showed that the spatial distribution of major ions, EC, TDS, TH and PI values in these samples significantly differ from one location to another due to geological variations and anthropogenic activities of the area. The quality of most groundwater is generally unfit for drinking due to their PI, EC, TH, calcium, potassium, total iron and bicarbonate (HCO3 −) values that found to be above the permissible limits of WHO and Ethiopian standards. The parameters like sodium percentage, sodium adsorption ratio (SAR), residual sodium bicarbonate, permeability index, magnesium hazard and Kelly’s ratio revealed good quality of groundwater for irrigation utilization, whereas EC of irrigation water (ECiw), combined effects of ECiw − SAR and bicarbonate hazard values indicated that majority of groundwater are not suitable for irrigation use. Piper trilinear diagram classified majority of samples under temporary hardness with Ca–Mg–HCO3 type. Further, Gibbs diagram reveals that water–rock interaction is the major hydrogeochemical processes governing the water chemistry of the study area. Therefore, it is recommended to perform a constant water quality checking program and improvement of tangible management practices for sustainable utilization of groundwater resources.